Effects of combination therapy with Bunium persicum and Foeniculum vulgare extracts on patients with polycystic ovary syndrome - Fatemeh Aliakbari; Misa Naghdipour Mirsadeghi; Elmira Hashemi; Mohammad Rahimi-Madiseh; Belgheis Mohammadi (Advanced Biomedical Research, 2022)
Background: Considering the side effects of common drugs used to treat polycystic ovary syndrome (PCOS), researchers have turned their attention to natural compounds, including medicinal plants. Foeniculum vulgare has estrogenic properties and has been traditionally used to treat gynecological disorders. Bunium persicum has medical aspects that have not yet been evaluated, so the aim of this study was to evaluate the effects of combination therapy with these extracts on clinical symptoms of women with PCOS. Materials and Methods: In this double-blind clinical trial study, 70 women with PCOS referred to infertility clinics, were selected and randomly divided into two groups. The intervention group received B. persicum capsule 60 mg plus F. vulgare capsule 25 mg) twice daily for 4 months and the control groups received routine intervention. Before and after the intervention, levels of luteinizing hormone (LH), follicle-stimulating hormone, progesterone, prolactin, testosterone and dehydroepiandrosterone sulfate (DHEAS) levels, hirsutism score, and menstrual pattern were recorded and endometrial thickness and follicle count were determined by ultrasound. Data were analyzed by the SPSS21 software. Results: Treatment with B. persicum and F. vulgare extracts significantly decreased LH and DHEAS levels, hirsutism score, and significantly increased menstrual duration compared to the control group. Before the intervention, 5.7% of the intervention and control groups had the normal menstrual pattern, while after the intervention 31.4% of the intervention group and 25.7% of the control group had the normal pattern. Conclusion: Regarding the effect of these extracts combination and because they have no side-effects, which is a great advantage over chemical drugs, using of these plants recommend.